Introduction to the smart grid : concepts, technologies and evolution - Salman, S. K. (Institution of Engineering and Technology, 2017)
This book identifies and discusses the tools required to ensure the interoperability among the various digitally-based components of the Smart Grid.
Keywords: Smart power grids.; elektronické knihy; electronic books